Wpływ podwyższonych koncentracji CO2 na wzrost ryzomorfów opieńki ciemnej Armillaria ostoyae (Romagn.) Herink w doświadczeniu in vitro - Lech, Paweł; Żółciak, Anna (Leśne Prace Badawcze, 2017)
A comparative experiment was carried out in growth chambers to determine the effects of elevated CO 2 concentrations (either 760 ppm or 1140 ppm) versus ambient CO 2 conditions on the growth of Armillaria ostoyae (Romagn.) Herink rhizomorphs, which is the infectious organ of a fungal pathogen affecting many forest trees. We found that one out of three isolates in the experiment differed significantly in rhizomorph production, which was measured as rhizomorph dry mass/100 days of growth. Rhizomorph production was also affected by the tree species used as a food source in the inoculum preparation, with beech wood being significantly different from oak and hazel. Under higher CO 2 regimes the production of rhizomorphs was consistently lower for all three isolates compared to ambient CO 2 concentrations. For one isolate (no. 11) the growth differences were significant between 380 ppm and both elevated CO 2 concentrations (760 ppm and 1140 ppm), while for the other two (no. 30 and 32) significance was observed only between 380 ppm and 760 ppm. No statistically significant differences have been noted between 760 ppm and 1140 ppm CO 2 for these two isolates. It was concluded that elevated concentrations of CO 2 inhibited A. ostoyae rhizomorph growth and therefore have the potential to lessen the pathogenicity of the fungus.